2017
DOI: 10.1093/eurheartj/ehx162
|View full text |Cite
|
Sign up to set email alerts
|

Low-density lipoprotein cholesterol targeting with pitavastatin + ezetimibe for patients with acute coronary syndrome and dyslipidaemia: the HIJ-PROPER study, a prospective, open-label, randomized trial

Abstract: AimsTo elucidate the effects of intensive LDL-C lowering treatment with a standard dose of statin and ezetimibe in patients with dyslipidaemia and high risk of coronary events, targeting LDL-C less than 70 mg/dL (1.8 mmol/L), compared with standard LDL-C lowering lipid monotherapy targeting less than 100 mg/dL (2.6 mmol/L).Methods and resultsThe HIJ-PROPER study is a prospective, randomized, open-label trial to assess whether intensive LDL-C lowering with standard-dose pitavastatin plus ezetimibe reduces cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(89 citation statements)
references
References 50 publications
0
85
0
4
Order By: Relevance
“…Further studies with larger sample sizes are needed to elucidate this issue. On the other hand, a recent clinical trial has shown that serum sitosterol level could be a good biomarker of ezetimibe efficacy 24 ) . Serum sitosterol has been shown as a surrogate marker of cholesterol absorption 25 ) .…”
Section: Sitosterol or Cholesterol?mentioning
confidence: 99%
“…Further studies with larger sample sizes are needed to elucidate this issue. On the other hand, a recent clinical trial has shown that serum sitosterol level could be a good biomarker of ezetimibe efficacy 24 ) . Serum sitosterol has been shown as a surrogate marker of cholesterol absorption 25 ) .…”
Section: Sitosterol or Cholesterol?mentioning
confidence: 99%
“…Ezetimibe is one of the appropriate drug therapies for patients with sitosterolemia 4,9,10) . A recent study, the Heart Institute of Japan-PRoper level of lipid lOwering with Pitavastatin and Ezetimibe in acute coRonary syndrome (HIJ-PROPER), has shown that serum sitosterol level, which is a surrogate marker of cholesterol absorption, can be a good biomarker for CHD prevention efficacy under ezetimibe therapy 11) . In a sub-analysis of HIJ-PROPER, the aggressive lipid-lowering treatment with ezetimibe had a preven-shown).…”
Section: Introductionmentioning
confidence: 99%
“…The lipid management strategy for secondary prevention is still changing in clinical practice from recent Japanese evidence. 21) REAL-CAD 22) Intervention…”
Section: Resultsmentioning
confidence: 99%
“…Recently two major outcome trials were reported from Japan. The HIJ-PROPER 21) study is a prospective, randomized, openlabel trial to assess whether intensive LDL-C lowering with standard-dose pitavastatin plus ezetimibe reduces cardiovascular events more than standard LDL-C lowering with pitavastatin monotherapy in patients with ACS and dyslipidaemia. Patients were randomized to intensive lowering (target LDL-C < 70 mg/dl); pitavastatin plus ezetimibe) or standard lowering (target LDL-C 90 mg/dl to 100 mg/dl); pitavastatin monotherapy).…”
Section: Clinical Evidence Of Aggressive Lipid Lowering In Secondarymentioning
confidence: 99%